The experience of good mentoring focused on overcoming turnover intention among millennial nurses - Jung, Seo-Yeon; Kim, Jung-Hee (Frontiers in Medicine, 2024)
Introduction Millennials are emerging as a prominent demographic in the nursing workforce. It is necessary to create an environment that harmonizes the advantages of each generation in a nursing workforce in which various generations coexist. As the importance of mentoring programs for millennial nurses grows, it is believed that the effectiveness of mentoring to support millennial nurses can be enhanced by identifying the attributes of good mentors as perceived by nurses. This study aimed to explore the attributes of good mentors according to millennial nurses in the nursing workforce with a focus on overcoming turnover intention problems. Methods Four focus group interviews were conducted to collect data, which were subsequently analyzed using Braun and Clarke’s thematic analysis method. A descriptive qualitative design involving 22 millennial nurses employed at a tertiary hospital, Hospital A, in Seoul, Republic of Korea was utilized. Results and discussion Four themes emerged from the analysis: the concept of a significant others, the presence of a driving force to endure, the importance of a guide to a harmonious life, and the value of a partner for growth. The participants themselves identified these themes. To prevent turnover intention among millennial nurses, mentors should employ diverse strategies, and institutional supports are crucial. Furthermore, since it is unrealistic to expect all ideal mentor characteristics to be present in one person, mentor development education is also necessary. This information is valuable for designing mentor development programs and for establishing a solid framework for effective mentoring programs.